Associations of diet and lifestyle factors with common volatile organic compounds in exhaled breath of average-risk individuals. (1st March 2019) - Krilaviciute, Agne; Leja, Marcis; Kopp-Schneider, Annette; Barash, Orna; Khatib, Salam; Amal, Haitham; Broza, Yoav Y; Polaka, Inese; Parshutin, Sergei; Rudule, Aiga; Haick, Hossam; Brenner, Hermann
Abstract: Background : Detection of diseases via exhaled breath remains an attractive idea despite persisting gaps in understanding the origin of volatile organic compounds (VOCs) and their relationship with the disease of interest. Data on factors potentially influencing the results of breath analysis remain rather sparse and often controversial. In this study, we aimed to investigate the associations of common VOCs in exhaled breath of average-risk individuals with socio-demographic and lifestyle factors, medical conditions as well as diet. Methods : Alveolar breath samples of 1447 men and women were collected in the morning after fasting and were analyzed using gas-chromatography linked with mass-spectrometry. Study participants were 40–64 years old, cancer-free, with overall good health status. The associations between selected VOCs and various factors determined from the questionnaire data were assessed using two-part-Wilcoxon test and Jonckheere–Terpstra trend test. Results : Fifteen VOCs where each of them was detected in at least 80% of the study population were included in this analysis. Statistically significant associations with various VOCs were demonstrated for gender and consumption of certain foods, such as coffee, leeks and garlic, while smoking was not associated with any of the analyzed compounds. Conclusion : Factors potentially modifying the composition of exhaled breath, such as dietary factors, deserve careful attention in the design and analysis of studies accessing the use of VOCs as diagnostic markers.